Domestic Saudi Arabian Travellers’ Understanding about COVID-19 and Its Vaccination - Najim Z. Alshahrani; Sultan M. Alshahrani; Shehata Farag; Harunor Rashid (Vaccines, 2021)
Background: There is a lack of data on Saudi domestic air travellers’ understanding regarding COVID-19 and their attitude towards the COVID-19 vaccination. Objectives: This study aimed to assess Saudi domestic air travellers’ understanding regarding COVID-19 and attitude towards mandating the COVID-19 vaccination for travellers. Methods: A survey using a self-administered, structured, and closed-ended questionnaire was conducted among domestic air travellers in Saudi Arabia. Participants’ socio-demographic information, travel history, health status, and attitudes and willingness to accept the COVID-19 vaccination were collected and analysed. Results: Of the 2236 respondents who participated in the survey, 542 (24.25%) had a history of COVID-19, 803 (35.9%) were exposed to a COVID-19 case, 1425 (63.7%) were concerned about catching COVID-19 during air travel, 796 (35.6%) thought the COVID-19 vaccination should be obligatory for travellers, 1105 (49.4%) thought it should be optional, and 335 (15.0%) thought the vaccination was unnecessary. Being of the male gender (adjusted odds ratio [aOR] 1.41, 95% confidence interval [95% CI] 1.14–1.69), being concerned about contracting COVID-19 (aOR 1.34, 95% CI 1.12–2.10) and frequent travelling (aOR 1.40, 95% CI 1.10–3.40) were predictors of vaccination uptake. Conclusion: This study demonstrates that although domestic Saudi travellers were concerned about COVID-19 infection, vaccine hesitancy was prevalent among them.